Erythema nodosum and primary tuberculosis - Case Report - Ovčina, Irma (Scripta Medica, 2019)
Abstract Erythema nodosum is a type of panniculitis, typically manifested as erythematous nodules. We reported a case of a young woman who presented with erythema nodosum and isolated unilateral axillar lymphadenopathy. Excision and biopsy have showed chronic granulomatous inflammation, in the first place tuberculosis. A extensive workup did not reveal any other focal points of tuberculosis. She has been successfully treated with antituberculotic therapy. Our case suggests that tuberculosis should be a part of the differential diagnosis in any case of erythema nodosum with isolated unilateral lymphadenitis. Key words: erythema nodosum, tuberculosis, lymphadenopathy